Testosterone deprivation accelerates cardiac dysfunction in obese male rats - Pongkan W. (2017)
© 2016 Society for Endocrinology. Low testosterone level is associated with increased risks of cardiovascular diseases. As obese-insulin-resistant condition could impair cardiac function and that the incidence of obesity is increased in aging men, a condition of testosterone deprivation could aggravate the cardiac dysfunction in obese-insulin-resistant subjects. However, the mechanism underlying this adverse effect is unclear. This study investigated the effects of obesity on metabolic parameters, heart rate variability (HRV), left ventricular (LV) function, and cardiac mitochondrial function in testosterone-deprived rats. Orchiectomized or shamoperated male Wistar rats (n = 36 per group) were randomly divided into groups and were given either a normal diet (ND, 19.77% of energy fat) or a high-fat diet (HFD, 57.60% of energy fat) for 12 weeks. Metabolic parameters, HRV, LV function, and cardiac mitochondrial function were determined at 4, 8, and 12 weeks after starting each feeding program. We found that insulin resistance was observed after 8 weeks of the consumption of a HFD in both sham (HFS) and orchiectomized (HFO) rats. Neither the ND sham (NDS) group nor ND orchiectomized (NDO) rats developed insulin resistance. The development of depressed HRV, LV contractile dysfunction, and increased cardiac mitochondrial reactive oxygen species production was observed earlier in orchiectomized (NDO and HFO) rats at week 4, whereas HFS rats exhibited these impairments later at week 8. These findings suggest that testosterone deprivation accelerates the impairment of cardiac autonomic regulation and LV function via increased oxidative stress and impaired cardiac mitochondrial function in obese-orchiectomized male rats.